2014
DOI: 10.1063/1.4865208
|View full text |Cite|
|
Sign up to set email alerts
|

Upper bounds for flexoelectric coefficients in ferroelectrics

Abstract: Flexoelectric effect is the response of electric polarization to the mechanical strain gradient. At the nano-scale, where large strain gradients are expected, the flexoelectric effect becomes appreciable and may substitute piezoelectric effect in centrosymmetric materials. These features make flexoelectricity of growing interest during the last decade. At the same time, the available theoretical and experimental results are rather contradictory. In particular, experimentally measured flexoelectric coefficients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 12 publications
3
46
0
Order By: Relevance
“…It has been found that flexoelectric coefficients are particularly large in materials with high dielectric constants, such as ferroelectrics 9,11,[13][14][15] . However, the magnitude of these coefficients greatly exceeds theoretical estimates 1, 16,17 . This discrepancy has lead to a controversy in the field of flexoelectricity, demanding further investigations into the quantification of the flexoelectric response 18 .…”
Section: Introductionmentioning
confidence: 85%
“…It has been found that flexoelectric coefficients are particularly large in materials with high dielectric constants, such as ferroelectrics 9,11,[13][14][15] . However, the magnitude of these coefficients greatly exceeds theoretical estimates 1, 16,17 . This discrepancy has lead to a controversy in the field of flexoelectricity, demanding further investigations into the quantification of the flexoelectric response 18 .…”
Section: Introductionmentioning
confidence: 85%
“…According to order-of-magnitude estimates 30,34,35 and ab initio calculations in perovskites 36 , the values of the components of the f tensor in perovskites are expected to be about 1 − 10 V. Thus, we see that ferroelectric perovskites are not far from the modulation instability. The fact that the apparent "pushing down", or renormalizing of the TA mode in PZO is much more pronounced than in other studied systems suggests that it could be the prime candidate in the search for materials where the modulation instability "would be found".…”
Section: Modulation Instabilitymentioning
confidence: 96%
“…For typical perovskite ferroelectrics BaTiO 3 and SrTiO 3 , using experimental data [31][32][33] , these criteria can be substantialized 30 as |f 44 | < 3.3 V, |f 11 − f 12 | < 7 V and |f 44 | < 2.4 V, |f 11 − f 12 | < 10 V, respectively. According to order-of-magnitude estimates 30,34,35 and ab initio calculations in perovskites 36 , the values of the components of the f tensor in perovskites are expected to be about 1 − 10 V. Thus, we see that ferroelectric perovskites are not far from the modulation instability.…”
Section: Modulation Instabilitymentioning
confidence: 99%
“…In a recent paper, 8 it is concluded that this is approximately the upper limit of the flexoelectricity strength that can be achieved in ionic crystals.…”
mentioning
confidence: 99%
“…12 Some of the above-cited authors state that the origin of this big discrepancy between the theory and experiment is at present not understood; others relate it to crystal imperfections assuming that in the paraelectric BaTiO 3 , there are polar islands that are reoriented by the strain gradient. An expert conclusion 8 states that "The magnitude of upper bonds obtained suggest that the anomalously high flexoelectricity coupling documented for perovskites ceramics can hardly be attributed to a manifestation of the static bulk effect." But in a more recent paper, 13 using a variety of experimental procedures including pyroelectric current, it is shown that the effect is intrinsic (bulk), and it is due to some polar formations in dielectric solids that exist beyond (and independent of) the external strain.…”
mentioning
confidence: 99%